Etnomatematika Pada Istana Kerajaan Amanuban (Sonaf Son Besi) - Hermina Amul; Ulfa Badu; Yafet Alunat; Uke Ralmugiz (Pendidikan Matematika Universitas Muhammadiyah Bangka Belitung, 2019)
This study aims to describe ethnomatematics studies at the Amanuban Royal Palace (SonafSon Besi). This type of research is qualitative research with ethnographic methods that aim to uncover mathematical ideas contained in the Amanuban Royal Palace (Sonaf Son Besi). This research was carried out in the Royal Palace of Amanuban located in Niki-Niki, TTS, NTT, Indonesia. The data collection techniques of this research were interview, documentation, and observation. Futhemore the data analysis technique used descriptive analysis, with stages of data reduction, data display, and making conclusions. The results of this study show the number of mathematical concepts that exist in Sonaf Son Besi as the AmanubanRoyalPalace such as: Solid Figure, Plane Figure and Congruence, very suitable for learning the material in terms of describing elements, finding building patterns, and Congruence.